Effects of Performance Pay Programs for Primary and Secondary Teachers on Student Academic Achievement: A Meta-Analysis Based on Experimental and Quasi-Experimental Studies - Yang, Jing (Best Evidence in Chinese Education, 2026)
Drawing on the analytical frameworks of principal-agent theory and team production theory, this study seeks to examine the effects of performance pay programs for primary and secondary teachers on student academic achievement and relevant moderating factors, using meta-analysis techniques. The analysis is based on 312 effect sizes from 33 studies with experimental or quasi-experimental design.